(untitled) (Dissertation Nursing, 2023)
INTRODUCTION: The international literature shows that 20-40% of patients with cognitive impairment, hospitalized in long-term facilities, may react during nursing care with aggressive behaviors such as screaming, threats, kicks, punches and scratches. The objective of this study is to validate in Italian the "Care Recipient Behavior Assessment Scale" (CAREBA), an assessment tool designed to measure physical and verbal aggression of the person with dementia. METHODS: The CAREBA was back-translated through an observational study. It was administered to a sample of dementia patients with physical and/or verbal aggressive behaviors, conducted in a hospital in Northern Italy . Reliability and validity were assessed. RESULTS: The scale shows satisfactory internal consistency (Cronbach’s Alpha = 0.79) and content validity (CVI-S= 90%). CONCLUSIONS: The CAREBA scale is a valid and reliable tool to detect aggression in patients with dementia.